ANALISIS ASUHAN KEPERAWATAN DENGAN ORAL HYGIENE MENGGUNAKAN SIWAK SEBAGAI UPAYA PENCEGAHAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) PADA PASIEN DI INTENSIVE CARE UNIT - Syifa Putri Salsabila (2023)
Ventilator-Associated Pneumonia (VAP) is one of the most common types of Healthcare Associated Infections (HAIs) that occurs in patients in the ICU due to the use of mechanical ventilation for >48 hours. VAP can increase the severity of the disease, extend length of stay patients, and increase the mortality rate. Oral hygiene is part of the prevention strategy in the VAP bundle. Oral health is the main component for the prevention of VAP because the mouth is the gateway for bacteria to enter and the main place for bacterial colonization. This scientific paper aims to analyze the results of oral hygiene interventions using siwak as VAP prevention in patients in the ICU. After intervention for five consecutive days twice a day, there was a decrease in the BOAS score which indicated an increase in the patient's oral health, and a decrease in the CPIS score with the interpretation that there was no development of VAP in the patient. It is hoped that oral hygiene using siwak can be used as the newest strategy and an alternative ingredient besides chlorhexidine to prevent VAP in patients in the ICU.